Ответы и объяснения

  • Участник Знаний
2014-01-16T19:18:25+04:00
1) P1 (X ) + P2 ( X ) =
= 5X^2 - 4X + 1 + 6X^2 + X - 3 = 11X^2 - 3X - 2 
2) P1 (X ) - P2 ( X ) =
= 5X^2 - 4X + 1 - 6X^2 - X + 3 = - X^2 - 5X + 3 
........................................................................
X^2 + (5X - 2) - (3X + 1 ) = 3X + X^2 
X^2 + 5X - 2 - 3X - 1 = 3X + X^2 
X^2 + 2X - 3 - 3X - X^2 = 0 
- X - 3 = 0
X = - 3 
обозначение степени
Комментарий удален
Комментарий удален
Комментарий удален
Комментарий удален